The Implementation of S-curve Acceleration and Deceleration Using FPGA - Guangyou Yang; Zhijian Ye; Yurong Pan; Zhiyan Ma (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper analyzes the basic principle of S-curve acceleration and deceleration, and presents an implementation method of S-curve control algorithm based on FPGA. The S-curve function module diagram and implementing method of PWM speed adjusting are described in FPGA. The steps of S-curve speed dissociation module and PWM variable frequency speed control are shown in this paper. High Performance and Capacity Mixed HDL Simulation software – ModelSim is used to verify the algorithm Verilog HDL code executed in FPGA. At last, a test experiment utilizing such algorithm mentioned above is carried out on one x-y working stand. There is a good agreement between simulation and experiment. The experimental results indicate that the algorithm is simple and reliable enough to meet different application requirements. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1897